2018
DOI: 10.1186/s12889-018-5470-1
|View full text |Cite
|
Sign up to set email alerts
|

Gender-dependent association between sleep duration and overweight incidence in CHINESE school children: a national follow-up study

Abstract: BackgroundThe relationship between sleep duration and overweight risk remains unexplored among Chinese children. This study aims to evaluate this association in a national investigation with school-aged population.MethodsThere were 18,302 normal weight children in this Chinese national study which conducted during 2013–2014 included in the research. Anthropometric measurements were performed both at baseline and after 6–9 month. Sleep duration, physical activity, food intake and social economic information wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 42 publications
1
15
1
Order By: Relevance
“…There was a significant difference between sleep duration and age group; namely, short sleep duration was more commonly found in the 16-18year age group. Similar results were also found in several previous studies [15,16,17,18].…”
Section: Discussionsupporting
confidence: 93%
“…There was a significant difference between sleep duration and age group; namely, short sleep duration was more commonly found in the 16-18year age group. Similar results were also found in several previous studies [15,16,17,18].…”
Section: Discussionsupporting
confidence: 93%
“…Future studies should use comparable data to monitor SLP levels among Chinese schoolchildren to help promote schoolchildren obtaining appropriate sleep durations on a regular basis. This study found that the frequency of meeting SLP guidelines declined significantly with increases in grades, which can be explained by heavier academic pressure [36]. Increasing grades, regardless of family income, indicate that schoolchildren face excessive academic loads, with consequent decreases in their SLP durations.…”
Section: Discussionmentioning
confidence: 69%
“…Some studies proposed a U-shaped [12,13] or linear inverse correlation [14] between sleep duration and obesity, however, some studies proposed no correlation between them [15,16]. Meanwhile, the association between short sleep duration and the overweight/obesity was somehow affected by sex [17], in which the sex was considered a speci c trait for short sleep duration in these with overweigh/obesity [18,19]. In this study, we aimed to investigate the prevalence of short sleep duration among students in Fuzhou.…”
Section: Introductionmentioning
confidence: 99%